Epilepsy‐related stigma and attitudes: Systematic review of screening instruments and interventions ‐ Report by the International League Against Epilepsy Task Force on Stigma in Epilepsy. Issue 3 (5th January 2022) - Austin, Joan K.; Birbeck, Gretchen; Parko, Karen; Kwon, Churl‐Su; Fernandes, Paula T.; Braga, Patricia; Fiest, Kirsten M.; Ali, Amza; Cross, J. Helen; de Boer, Hanneke; Dua, Tarun; Haut, Sheryl R.; et al.
Summary: Objective: This is a systematic review aimed at summarizing the evidence related to instruments that have been developed to measure stigma or attitudes toward epilepsy and on stigma‐reducing interventions. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) standards. A broad literature search (1985–2019) was performed in 13 databases. Articles were included if they described the development and testing of psychometric properties of an epilepsy‐related stigma or attitude scale or stigma‐reducing interventions. Two reviewers independently screened abstracts, reviewed full‐text articles, and extracted data. Basic descriptive statistics are reported. Results: We identified 4234 abstracts, of which 893 were reviewed as full‐text articles. Of these, 38 met inclusion criteria for an instrument development study and 30 as a stigma‐reduction intervention study. Most instruments were initially developed using well‐established methods and were tested in relatively large samples. Most intervention studies involved educational programs for adults with pre‐ and post‐evaluations of attitudes toward people with epilepsy. Intervention studies often failed to use standardized instruments to quantify stigmatizing attitudes, were generally underpowered, and often found no evidence of benefit or the benefit was not sustained. Six intervention studies with stigma as the primary outcome had fewer design flaws and showed benefit. Very few or no instruments were validated for regional languages or culture, and there were very few interventions tested in some regions. Significance: Investigators in regions without instruments should consider translating and further developing existing instruments rather than initiating the development of new instruments. Very few stigma‐reduction intervention studies for epilepsy have been conducted, study methodology in general was poor, and standardized instruments were rarely used to measure outcomes. To accelerate the development of effective epilepsy stigma‐reduction interventions, a paradigm shift from disease‐specific, siloed trials to collaborative, cross‐disciplinary platforms based upon unified theories of stigma transcending individual conditions will be needed.